Economics of combined nuclear-gas power generation - Florido, P. E. (2000)
An assessment of the economy of combined nuclear–gas power plants was presented. The combined  thermal cycle is viewed as a convenient ‘strategic alliance’ between both types of fuels (nuclear and natural gas), which offers an alternative of electric power generation at lower costs. It was shown that the dominant economic parameters are the gas price and the capital costs of nuclear power plants. Contrary to the trends followed from classical assessments of nuclear and gas power generation taken separately, the maximization of the superheated temperature was not found to be a good design criterion. In dealing with situations where gas prices are high, the optimum superheating can result lower than the technically achievable. Moreover, within rather wide cost ranges, the combination of nuclear and gas presents interesting possibilities to successfully compete in the near future electric market.